International register “Dynamics analysis of comorbidities in SARS-CoV-2 survivors” (AKTIV SARS-CoV-2): analysis of 1,000 patients - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; Y. N. Belenkov; A. O. Konradi; Y. M. Lopatin; S. N. Tereshchenko; A. P. Rebrov; A. I. Chesnikova; I. V. Fomin; N. V. Grigorieva; M. V. Boldina; et al. (Российский кардиологический журнал)
COVID-19 is a severe infection with high mortality. The concept of the disease has been shaped to a greater extent on the basis of large registers from the USA, Spain, Italy, and China. However, there is no information on the disease characteristics in Caucasian patients.Therefore, we created an international register with the estimated capacity of 5,000 patients — Dynamics Analysis of Comorbidities in SARS-CoV-2 Survivors (AKTIV SARS-CoV-2), which brought together professionals from the Russian Federation, Republic of Armenia, Republic of Kazakhstan, and Kyrgyz Republic. The article presents the first analysis of the register involving 1,003 patients. It was shown that the most significant difference of the Caucasian population was the higher effect of multimorbidity on the mortality risk vs other registers. More pronounced effect on mortality of such diseases as diabetes, obesity, hypertension, chronic kidney disease, and age over 60 years was also revealed.